Association of dental trauma experience and first-aid knowledge among rugby players in Malaysia - Abdullah, D.; Liew, A.K.C.; Noorina, W.A.W.; Khoo, S.; Wee, F.C.L. (Blackwell Publishing, 2015)
Objectives To assess and compare the knowledge of rugby players regarding first-aid measures for dental injuries.